The effectiveness of non-pharmacological interventions in the management of symptom clusters in adult cancer patients: a systematic review protocol. (April 2016) - Nguyen, Ly Thuy; Yates, Patsy; Annoussamy, Lourdes Clemenceau; Truong, Trung Quang
Abstract : Review question/objective: To what extent are non-pharmacological interventions effective in reducing symptom clusters in terms of presence, frequency and severity, compared with standard care? More specifically, the objectives are to: Identify the effectiveness of non-pharmacological interventions in reducing symptom clusters in terms of presence, frequency, distress and severity, and their impacts on adult cancer patients. Examine the characteristics of effective interventions (e.g. intervention components, delivery methods and clinical contexts) in decreasing symptom clusters in terms of presence, frequency and severity, and their impacts on adult cancer patients. Center conducting the review: The Hanoi Medical University Nursing Research Center for Evidence Based Health Care: a Collaborating Centre of the Joanna Briggs Institute; and Centre for Evidence-based Healthy Aging: an Affiliate Centre of the Joanna Briggs Institute, School of Nursing, Queensland University of Technology, Australia.